The Strategic Role Of The Head Of The National Road Implementation Agency (BPJN) Palangkaraya In Managing The Risk Of Infrastructure Project Delays - Abdul Aziz Ahmad Faris; Achmad Syamsudin; Gema Borneo Poetra; Jonathan Giovanni (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Infrastructure development is one of the Indonesian government’s top priorities to support economic growth and promote equitable development across regions. However, project delays remain a significant challenge that hinders the effectiveness of national strategic programs. This study aims to analyze the strategic role of the Head of the National Road Implementation Agency (BPJN) Palangkaraya in managing the risk of delays in infrastructure projects, particularly national road projects in Central Kalimantan. The research employs a qualitative approach with a case study design, involving in-depth interviews with the Head of BPJN and several project implementation officials as key informants. Data were analyzed using thematic analysis to identify patterns of strategic decision-making in responding to project uncertainties. The results reveal that decision-making processes are carried out through a combination of rational and intuitive approaches, taking into account technical aspects, fiscal policies, and external factors such as weather conditions and material distribution. The Head of BPJN acts as an adaptive decision-maker who balances national interests with field realities. This study underscores the importance of risk-based strategic leadership in improving the performance of public infrastructure projects.